2009
DOI: 10.2193/2007-524
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Detection Probabilities of Waterfowl Broods From Ground‐Based Surveys

Abstract: Brood:pair ratios could provide an economical method for assessing spatial or temporal variation in waterfowl productivity, but such estimators are severely biased by incomplete detection of broods. We conducted 3 sequential counts of 1,357 waterfowl broods in northeastern North Dakota, USA, and used closed‐population mark‐recapture models to estimate total brood abundance while controlling for variation in detection probabilities (p). Blue‐winged teal (Anas discors) broods had the lowest average detection pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…The main findings of this paper are that (a) the probability of detecting singing males within the framework of traditional aural point-count protocols was low compared to other bird species (Eraud et al 2007;Gonzalo-Turpin et al 2008;Pagano and Arnold 2009) and (b) the additional use of playback strongly increased detectability, therefore improving the accuracy of abundance estimates. We observed differences in detectability between the 2 years, with higher values recorded in 2009.…”
Section: Discussionmentioning
confidence: 93%
“…The main findings of this paper are that (a) the probability of detecting singing males within the framework of traditional aural point-count protocols was low compared to other bird species (Eraud et al 2007;Gonzalo-Turpin et al 2008;Pagano and Arnold 2009) and (b) the additional use of playback strongly increased detectability, therefore improving the accuracy of abundance estimates. We observed differences in detectability between the 2 years, with higher values recorded in 2009.…”
Section: Discussionmentioning
confidence: 93%
“…This was the most parameterized (about four sample points per model parameter) of the six models. We also modeled the influence of habitat type (p(HABITAT)), observer identity (p(OBSERVER)), and time of day (p(STARTTIME)) on detection probability, as all of these factors can influence the potential detectability of numerous bird species (Chandler et al, 2009;Darrah and Krementz, 2009;Gonzalo-Turpin et al, 2008;King et al, 2009a,b;Mitchell and Donovan, 2008;Pagano and Arnold, 2009;Ruiz-Gutiérrez et al, 2010;Skirven, 1981). We converted habitat cover and point count start times into standard normal deviates (z-scores) to help facilitate convergence of the numerical optimization algorithm, and modeled observers as categories (observer 1 vs. 2).…”
Section: Habitat Association Analysismentioning
confidence: 99%
“…Royle and Nichols (2003) suggested that 10 surveys can produce good model abundance estimates even for bird species with low detection probability. An effort of three surveys, as suggested by the Northeast Shrubland Bird Workgroup and elsewhere (Field et al, 2005;MacKenzie and Royle, 2005;Pagano and Arnold, 2009;Tyre et al, 2003) as a general rule, may be insufficient for shrubland birds in pine barrens. Note, however, that because detectability tends to vary by habitat type or structural characteristics (Chandler et al, 2009;Chace et al, 2009;Darrah and Krementz, 2009;GonzaloTurpin et al, 2008;Mitchell and Donovan, 2008;Ruiz-Gutiérrez et al, 2010), sample points located in habitat where a species is more detectable may require fewer surveys.…”
Section: Survey Effortmentioning
confidence: 99%
See 2 more Smart Citations